IMPROVEMENT OF TECHNICAL TRAINING MATERIALS FOR ROAD AND BRIDGE PRESERVATION SUPERVISORS IN THE CONCRETE PAVEMENT PRESERVATION MODULE (RIGID PAVEMENT) IN AN EFFORT TO IMPROVE ROAD PAVEMENT PERFORMANCE - Ajang Zaenal Afandi (Bajang Institute, 2024)
The West Java Province Human Resources Development Agency (BPSDM). in collaboration with Pusbangkom Roads, Settlements and Regional Infrastructure Ministry PUPR, Technical Training Materials for Road and Bridge Preservation Supervisors deemed necessary refined with the aim of, among other things (1) improving the material in the Preservation Module Concrete pavement (2) know what factors can cause deficiencies perfecting the material by validating what modules and strategies are possible maximizing the understanding of training participants so that they can carry out learning well (3). Finding an effective learning method for designing layers Fast track concrete pavement with a concrete age of 7 days can open traffic. This research uses approach research and development. using data analysis techniques from trial results theory Close Technique, while research subjects on learning outcome indicators have not increased material information about concrete design fast track (oven traffic 7 days) by viewing various phenomena, (1) from the systematic assessment of training and learning curricula; target training participants, training organizers, approach to delivering material, methods learning (2) if there is a demand for faster concrete pavement preservation work (open traffic 7 days), repair of damaged concrete pavement and quality control. Module validity content tested by experts in the field and readability by users (training alumni) with distribute questionnaires using Close Technique . The module is acceptable in terms of validity fill in via expert judgement; while the validity of implementation in experimental trials the laboratory shows that all categorized submodules can be implemented (3) Improvements to the concrete pavement preservation module were carried out by adding concrete SOPsn fast-track .Human Resources Development Agency (BPSDM) West Java Province and Pusbangkom for Roads, Settlements and Regional Infrastructure BPSDM Ministry of Works General, to be able to consider proposals for improvements to Road Preservation Training materials and Bridge on Concrete Pavement Preservation Module